Recombinants between endogenous and exogenous avian tumor viruses: role of the C region and other portions of the genome in the control of replication and transformation. - Tsichlis, P N (1980)
Endogenous retroviruses of chickens are closely related to exogenous viruses isolated from spontaneous tumors in the same species, yet differ in a number of important characteristics, including the ability to transform cells in culture, ability to cause sarcomas or leukemias, host range, and growth rate in cell culture. To correlate these differences with specific sequence differences between the two viral genomes, the genome RNA of transforming subgroup E recombinants between the Prague strain of Rous sarcoma virus, subgroup B (Pr-RSV-B), and the endogenous Rous-associated virus-0 (RAV-0), Subgroup E, and seven nontransforming subgroup E recombinants between the transformation-defective mutant of Pr-RSV-B and RAV-0 was examined by oligonucleotide fingerprinting. The pattern of inheritance among the recombinant viruses of regions of the genome in which Pr-RSV-B and RAV-0 differ allowed us to draw the following conclusions. (i) Nonselected parts of the genome were, with a few exceptions, inherited by the recombinant virus progeny randomly from either parent, with no obvious linkage between neighboring sequences. (ii) A small region in the Pr-RSV-B genome which maps in the 5' region was found in all transforming but only some of the nontransforming recombinants, suggesting that it plays a role in the control of the expression of transformation. (iii) A region of the Pr-RSV-B genome which maps between env and src was similarly linked to the src gene and may be either part of the structural gene for src or a control sequence regulating the expression of src. (iv) The C region at the extreme 3' end of the virus genome which is closely related in all the exogenous avian retroviruses but distinctly different in the endogenous viruses is the major determinant responsible for the differences in growth rate between RAV-0 and Pr-RSV-B. This latter observation allowed us to redefine the C region as a genetic locus, c, with two alleles cn (in RAV-0) and cx (in exogenous viruses).